Design Thinking Approach in Designing Animal Care Services Based on Applications - Safira, Handini Mirna; Marthadinata, Agung; Cahyawan, Risky Dwi (Universitas Mercu Buana, 2025)
This study aims to design a digital-based pet care service application to improve accessibility and service efficiency for pet owners in the Greater Jakarta area (Jabodetabek). The design thinking approach was used as the primary framework, consisting of five stages: empathize, define, ideate, prototype, and test. This study's implementation reached the prototype stage, presenting an initial visualization of the platform based on user needs. The business model was developed using the Business Model Canvas (BMC), covering nine key elements from key partners to revenue streams. Data were collected through questionnaires distributed to 45 pet owners in Jabodetabek using a purposive sampling technique and analyzed using qualitative and quantitative methods. The results indicate that most respondents face obstacles in accessing pet care services. Consequently, they expressed the need for several key features within the application to better facilitate their needs. The digital pet care business model was designed to address these demands by integrating various services into a single digital platform. Through the design thinking approach, the proposed solution is expected to enhance user experience and expand the reach of pet care services in Indonesia.